Assessment and Management of Infection in Alcoholic Hepatitis - Vergis, Nikhil; Atkinson, Stephen R.; Thursz, Mark R. (Seminars in Liver Disease, 2020)
Severe alcoholic hepatitis (SAH) is a condition characterized by jaundice and liver failure that develops after heavy and prolonged alcohol consumption. Infection frequently complicates the natural history of the disease and is independently associated with mortality. Objective recognition and recording of infection are therefore essential in the evaluation of therapeutic interventions and for antibiotic stewardship. This review will evaluate infections that complicate SAH at admission and beyond. Factors that associate with the development of infection will be identified and clinical and laboratory techniques available to identify infection will be discussed. Common pathogens and frequently used antibiotics will be reviewed and recommendations will be made for the management of infection for SAH patients. New techniques to assess infection earlier and more precisely may improve diagnosis and treatment of this important driver of mortality in SAH.
Keywords: alcoholic hepatitis; infection; polymerase chain reaction; systemic inflammatory response syndrome